Unique Presentation of Hematuria in a Patient with Arterioureteral Fistula - Tomas Mujo; Erin Priddy; John J. Harris; Eric Poulos; Mahmoud Samman (Case Reports in Radiology)
Active extravasation via an arterioureteral fistula (AUF) is a rare and life-threatening emergency that requires efficient algorithms to save a patient’s life. Unfortunately, physicians may not be aware of its presence until the patient is in extremis. An AUF typically develops in a patient with multiple pelvic and aortoiliac vascular surgeries, prior radiation therapy for pelvic tumors, and chronic indwelling ureteral stents. We present a patient with a left internal iliac arterial-ureteral fistula and describe the evolution of management and treatment algorithms based on review of the literature.